2010
DOI: 10.1038/npp.2010.223
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Treatment in Adolescent Rats with an Attention Deficit/Hyperactivity Disorder Phenotype: Cocaine Addiction Vulnerability and Dopamine Transporter Function

Abstract: Appropriate animal models of Attention Deficit/Hyperactivity Disorder (ADHD) and drug reinforcement allow investigation of possible underlying biological bases of ADHD and its co-morbidity with cocaine addiction. Toward this end, Spontaneously Hypertensive Rats (SHR) exhibiting an ADHD phenotype were compared to Wistar-Kyoto (WKY) and Wistar (WIS) rats. Initially, 1.5 mg/kg oral methylphenidate or vehicle was administered between post-natal days 28–55 and acquisition of visual discrimination learning was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
98
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(124 citation statements)
references
References 69 publications
(80 reference statements)
20
98
4
Order By: Relevance
“…47,48 Finally, there seems to be an inconsistency among preclinical studies showing no differences in rates of acquisition of cocaine reinforcement after chronic treatment with MPH. 21,22 Gill et al 35 explain this inconsistency by highlighting the differences in the dose of cocaine initially delivered to the animals in the self-administration paradigm. In this study, Gill et al 35 provided the animals with lower initial doses of cocaine, which were below reinforcing thresholds.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…47,48 Finally, there seems to be an inconsistency among preclinical studies showing no differences in rates of acquisition of cocaine reinforcement after chronic treatment with MPH. 21,22 Gill et al 35 explain this inconsistency by highlighting the differences in the dose of cocaine initially delivered to the animals in the self-administration paradigm. In this study, Gill et al 35 provided the animals with lower initial doses of cocaine, which were below reinforcing thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…In the first study, Peña et al 37 For instance, increases in the rewarding value of cocaine were observed in rodents submitted to cocaine selfadministration, 3,21 whereas animals (especially from the SHR strain) tested with the CPP task exhibit decreased rewarding effects. 37 To address this question, Crawford et al 22 Effects were only observed among male subjects that had been exposed to MPH and these effects were only observed in relation to cocaine self-administration.…”
Section: Studies Comparing the Effects Of Different Methodological Asmentioning
confidence: 99%
See 3 more Smart Citations